The effect of a single administration of streptozotocin on hippocampus metabolites in NODSCID mice - D. A. Tur; O. B. Shevelev; M. В. Sharapova; M. A. Zolotykh; A. E. Akulov (Вавиловский журнал генетики и селекции, 2018)
The significant increase in the number of people diagnosed with diabetes mellitus in recent years makes studies of this problem topical. The persistent hyperglycemia accompanying the development and course of type 1 diabetes mellitus (T1DM) can affect the func-tional and structural levels of the organization of the central nervous system. These changes may be mediated by metabolic aberrations. Magnetic resonance spectroscopy (MRS) is a common method of intravital detection of metabolic reactions. In this study, MRS of the hippocampus of NOD.CB17-Prkdcscid/NcrCrl mice (NODSCID) was performed 4 days after the administration of streptozotocin (STZ) to assess the effect of STZ itself, and 60 days after the administration of STZ to another group of animals to assess the effect of chronic hyperglycemia caused by the delayed effect of STZ, involving the death of pancreatic β-cells. The simulation of T1DM by STZ administration is used worldwide. Nevertheless, the question remains whether there is a short-term effect of the introduction of STZ at the level of hippocampal metabolites recorded by MRS. The comparison of experimental and control animal groups revealed no effect of STZ on metabolites in the hippocampus of NODSCID mice on day 4 after its administration. In contrast, another comparison of the experimental and control animals on day 60 after STZ administration showed elevated contents of alanine and taurine, and a reduced lactate content. Thus, the introduction of STZ itself does not affect the metabolism of the hippocampus, and MRS is a promising method for assessing the effect of T1DM on brain metabolism in animals.